DEVELOPMENT OF PEDAGOGICAL SYSTEMS IN SYNERGETIC DIMENSION (Pedagogy of Higher and Secondary Education, 2022)
In article features of development of pedagogical systems on the basis of deas synergetic are investigated. The author compares strategy of optimization and strateg development of systems. Effectiveness development of systems is defined self-organizing.
Keywords: pedagogical system; self-organizing; optimizations; innovatve development